1999
DOI: 10.1111/j.1749-6632.1999.tb08735.x
|View full text |Cite
|
Sign up to set email alerts
|

Squalene, Olive Oil, and Cancer Risk: Review and Hypothesis

Abstract: Epidemiologic studies of breast and pancreatic cancer in several Mediterranean populations have demonstrated that increased dietary intake of olive oil is associated with a small decreased risk, or no increased risk, of cancer, despite a high overall lipid intake. Experimental animal models in high dietary fat and cancer also indicate that olive oil either has no effect, or a protective effect, on the prevention of a variety of chemically induced tumors. As a working hypothesis, it is proposed that the high sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
201
0
13

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(215 citation statements)
references
References 31 publications
1
201
0
13
Order By: Relevance
“…Experimental animal model studies of high dietary fat and cancer have also indicated that olive oil can help prevent a number of chemically induced tumors (Weijl et al, 1997). It has been proposed that squalene, found in olive oil, has a protective effect (Newmark, 1997). A favorable effect of olive oil has also been proposed, on the basis of other animal experiments, to be due to the presence of oleic acid, a monounsaturated fatty acid, and specific micronutrients, such as vitamin E (Braga et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental animal model studies of high dietary fat and cancer have also indicated that olive oil can help prevent a number of chemically induced tumors (Weijl et al, 1997). It has been proposed that squalene, found in olive oil, has a protective effect (Newmark, 1997). A favorable effect of olive oil has also been proposed, on the basis of other animal experiments, to be due to the presence of oleic acid, a monounsaturated fatty acid, and specific micronutrients, such as vitamin E (Braga et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…66 Recent in vitro and in vivo model experiments suggest a tumour-inhibiting role for squalene. 67 Pr. Couvreur's team developed the concept of squalenoylation involving the chemical linkage of squalene with various nucleoside analogues which allowed the formation of novel colloidal nano-assemblies of 100-300nm with a narrow size distribution, after dispersion in an aqueous environment.…”
Section: Squalenoylationmentioning
confidence: 99%
“…farnesyl protein transferase (Kohl et al 1995, Reuveni et al 1997) or which act to lower Ras mRNA levels through the use of anti-sense oligonucleotides and ribozymes (Monia et al 1992, Kawada et al 1997, Scherr et al 1997. Many naturally occurring compounds also inhibit Ras function, often by preventing association with the membrane, including a Vinca alkaloid (Umezawa et al 1994), squalene (found in olive oil (Newmark 1997)), diallyl disulfide (found in garlic (Singh et al 1996)) and damnacanthal (Hiramatsu et al 1993).…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%